IMPLEMENTASI VIDEO EDITING SEBAGAI MEDIA PEMBELAJARAN PADA MATAPELAJARAN KEJURUAN DI KELAS XI SMK TV WATAMPONE - Karmila; Ahmad Nurul Ikhsan B; A. Suharman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of using learning media that can improve students’ involvement and practical skills in vocational learning. This study aimed to examine the implementation of video editing as a learning medium in vocational subjects for Grade XI students at SMK TV Watampone and to identify the teacher’s efforts in guiding students during the learning process. This study employed a qualitative approach and was conducted at SMK TV Watampone, Bone Regency, South Sulawesi. The study was based on the Learning by Doing and David Kolb’s Experiential Learning theories, which emphasize learning through direct experience and practice. Data were collected through observation, interviews, and documentation involving five students and one vocational subject teacher. The results showed that the use of video editing as a learning medium improved students’ involvement, creativity, practical skills, and understanding of vocational materials. The use of the CapCut application helped students learn directly through video production and editing activities. The teacher acted as a facilitator by providing guidance in using the application, developing video concepts, and solving technical problems. Therefore, the implementation of video editing provided a more engaging learning experience and supported the improvement of students’ practical skills and active participation in vocational learning. Keywords: Video Editing, Learning Media, Vocational Learning